Illiberal Norm Diffusion: How Do Governments Learn to Restrict Nongovernmental Organizations? (International Studies Quarterly, 2020)
Recent decades have witnessed a global cascade of restrictive and repressive measures against nongovernmental organizations (NGOs). We theorize that state learning from observing the regional environment, rather than NGO growth per se or domestic unrest, explains this rapid diffusion of restrictions. We develop and test two hypotheses: (1) states adopt NGO restrictions in response to nonarmed bottom-up threats in their regional environment ("learning from threats"); (2) states adopt NGO restrictions through imitation of the legislative behavior of other states in their regional environment ("learning from examples"). Using an original dataset on NGO restrictions in ninety-six countries over a period of twenty-five years (1992–2016), we test these hypotheses by means of negative binomial regression and survival analyses, using spatially weighted techniques. We find very limited evidence for learning from threats, but consistent evidence for learning from examples. We corroborate this finding through close textual comparison of laws adopted in the Middle East and Africa, showing legal provisions being taken over almost verbatim from one law into another. In our conclusion, we spell out the implications for the quality of democracy and for theories of transition to a postliberal order, as well as for policy-makers, lawyers, and civil-society practitioners.